Software and hardware complex of multilevel system of situational centers of the security and defense sector - Grechaninov, Viktor; Oksanich, Iryna; Lopushansky, Anatoly (Science-based technologies, 2021)
The article is devoted to solving the problem of creating a software and hardware complex (SHC) of an automated system of situational centers of state authorities of the security and defense sector (AS SC SA SDS). Relevance. The problem of creating intellectual SC for the SA SDS is nowadays extremely urgent, because the SDS is responsible for the national security of the state as a whole and separately for each citizen. Formulation of the problem. The work examines the system of the SC SDS for security forces as a multi-level one, which has three levels of management - strategic (state), operational and tactical. Since, from a technical point of view, the SC is a software and hardware complex designed for personal and collective analytical work of managers (commanders), the study of the problem of creating a standard software and hardware complex is a necessary component of research devoted to the automation of these structures. The aim of the work is to study the basic requirements for a typical SHC and its composition, which should ensure the functioning of the AS of the SC SA SDS at the strategic, operational and tactical levels of control in the security forces. Results. The paper analyzes the features and provides the requirements for the AS SC SA SDS. The spatial, organizational, informational, technical and software integration of the AC system components is considered. The requirements for informational, technical and software compatibility of the AC SC components are given. There is a list of types of AS that are deployed at different levels of management. The generalized architecture of the SC SDS system is shown, the composition of mathematical, hardware and software is proposed, which should be part of the standard hardware and software complex of the AS SC SA SDS. The basic modeling complex (BMC) is described as a means of simulation modeling of a typical software and hardware complex of the AS SC SDS, the model of which is formed using a systematic approach. The main capabilities and a brief description of the BMC subsystems are given. It is noted that to demonstrate the work of the BMC, a model has been created, which is deployed at the Institute of Mathematical Machines and Systems Problems of the NAS of Ukraine. On the model, using the example of the hierarchical structure of the Armed Forces of Ukraine, the work of the military command and control bodies of the strategic, operational and tactical levels is imitated. Conclusions. The results of the research can be used to create an automated system for the SC of state authorities in the security and defense sector.